Miscibility and properties of low molecular mass poly(l-lactide) and poly(methyl methacrylate) blends - Vidović, Elvira (Array, 2019)
Modification of biobased PLLA properties by mixing with conventional PMMA via melt mixing in Brabender mixer was performed. Despite negative results of theoretical miscibility calculations by the group contribution approach of Coleman, Graf and Painter, homogeneous blend morphologies were prepared as recorded with scanning electron microscopy (SEM). All PLLA/PMMA blends displayed a single glass transition temperature. With increasing fraction of PMMA in blends, the increase in Tg from 58 °C to 93 °C was recorded by differential scanning calorimetry (DSC). Added PMMA improved mechanical properties, while the flexibility of PLLA/PMMA blends gradually decreased as revealed by DMA measurements.